The American Constitution and the Spanish Constitutions of 1812 and 1978: Changes and structures explained through the uncertainty avoidance dimension and other cultural dimensions - Pacheco Baldó, Rosa María (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper analyses the American Constitution of 1787 and the Spanish Constitutions of 1812 and 1978. The objective is to analyse their structures and the changes they have undergone throughout history, to find differences that can be explained by the different cultural values that these two groups normally display. As will be seen, the cultural dimension of uncertainty avoidance, amongst others, is the one that has a greater presence in this study. The conclusions drawn from this study show that cultural groups change throughout history, but the cultural roots that they inherit seem to be present through the times.